2005
DOI: 10.1197/jamia.m1680
|View full text |Cite
|
Sign up to set email alerts
|

Communities' Readiness for Health Information Exchange: The National Landscape in 2004

Abstract: The authors analyzed data from 134 responses from communities in 42 states and the District of Columbia. Communities are enthusiastic about moving forward with health information exchange to create LHIIs to improve the efficiency, quality, and safety of care. They have identified significant local sources of investment and plan to use some clinical data standards but not as broadly as was expected. The communities have not yet developed the specific technical approaches or the sustainable business models that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 3 publications
1
54
0
Order By: Relevance
“…The introduction of IT, however, causes fundamental transformation in the delivery of health-care services, and organizational issues often present as large -if not larger -barriers to adoption (Overhage et al, 2005;. Small organizations, including critical access hospitals and physician practices operated by just one to three doctors, find it particularly hard to adopt and use health IT due to costs and a lack of knowledge in how to select, implement, and integrate IT into the delivery of health care.…”
Section: The Nrc Websitementioning
confidence: 97%
“…The introduction of IT, however, causes fundamental transformation in the delivery of health-care services, and organizational issues often present as large -if not larger -barriers to adoption (Overhage et al, 2005;. Small organizations, including critical access hospitals and physician practices operated by just one to three doctors, find it particularly hard to adopt and use health IT due to costs and a lack of knowledge in how to select, implement, and integrate IT into the delivery of health care.…”
Section: The Nrc Websitementioning
confidence: 97%
“…A notable increase in publications occurred after the Office of the National Coordinator for Health IT was established in 2004. 6 Although approximately half of peer-reviewed articles presented original findings (20 of 39; 51%), only 2 reported results from a randomized controlled trial 7,8 ; 8 others reported survey results, 4 described "case studies" of HIEs, 3 reported qualitative studies of HIE participants, and 2 analyzed cost. Expert opinion made up 26% of the peerreviewed publications in the form of 10 editorials, letters, and commentaries.…”
Section: Summary Description Of the Publicationsmentioning
confidence: 99%
“…This commitment must be underscored by the recognition and acceptance of the needs for both community health and individual privacy and confidentiality [42]. Health information exchange (HIE) systems illustrate the potential for distributed models for data collection and access with potentially dramatic impact on the practice of public health surveillance [43]. For example, the HIE in Indiana (USA) links payers, hospitals, laboratories, pharmacies, physician offices, ambulance centers, and public health departments throughout the state.…”
Section: Opportunities and Challenges In Public Health Surveillancementioning
confidence: 99%